Implementation of Perception Communication Construct of Sound and Rhythm in Children with Hearing Impairment: Case Study in Pre-School and Kindergarten - Seliana Dwi Rahmawati; Permanarian Somad; Imas Diana Aprilia (Department of Special Education, 2018)
Communication is very important in the life. The children that were born with hearing impairment get less access to speech acoustic information for detecting and discriminating among speech sounds. Therefore, some program is needed to develop the remaining hearing. Perception Communication Construct of Sound and Rhythm (Bina Komunikasi Persepsi Bunyi dan Irama/BKPBI) is a program that aims to develop the potential for hearing to communicate. The aim of this study wa to know the implementation of BKPBI at TK-LB Santi Rama in Jakarta. This study used qualitative method by collecting observation data from classroom and BKPBI program, and interviewing the principal and teachers in the school. The results showed that the school implemented BKPBI program in the big class, private class, and in BKPBI room. The school implemented three step program such as assessment, implementation and evaluation. Besides, There is individual and classical program for hearing and articulation program.